1996
DOI: 10.1080/10862969609547914
|View full text |Cite
|
Sign up to set email alerts
|

Reader-Based and Teacher-Centered Instructional Tasks: Writing and Learning about a Short Story in Middle-Track Classrooms

Abstract: This study describes how and what 2 classes of middle-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 11 publications
1
15
0
1
Order By: Relevance
“…The results of the study indicated that students who received reader-based tasks attained higher post-test scores compared to students who received teacher-centered instructional tasks. Newell (1996) further identified six literary response statements which were similar to the ones identified by earlier researchers such as Odell and Cooper (1976), Purves (1985) and Squire (1963). The six types of statements are: descriptive (retelling of story and description of aspects), personal reaction (reaction to form and content), associative (references to writers' experiences and knowledge), interpretive (statements that go beyond what are found in the story and inference is made), evaluative and miscellaneous.…”
Section: Literature Reviewsupporting
confidence: 75%
See 3 more Smart Citations
“…The results of the study indicated that students who received reader-based tasks attained higher post-test scores compared to students who received teacher-centered instructional tasks. Newell (1996) further identified six literary response statements which were similar to the ones identified by earlier researchers such as Odell and Cooper (1976), Purves (1985) and Squire (1963). The six types of statements are: descriptive (retelling of story and description of aspects), personal reaction (reaction to form and content), associative (references to writers' experiences and knowledge), interpretive (statements that go beyond what are found in the story and inference is made), evaluative and miscellaneous.…”
Section: Literature Reviewsupporting
confidence: 75%
“…A similar approach was also adopted by Newell (1996) by using writing tasks to analyze students' responses to a short story. Forty-five 10 th grade students were assigned to either reader-based or teacher-centered instructional tasks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Approaches to literature education in L1 and L2 Two general approaches to literature teaching have been distinguished: textoriented and reader-based approaches (Applebee, 1993;Newell, 1996). Textoriented approaches regard meaning as something that resides in a literary text: each text has a 'correct' interpretation, which may be unlocked by the teacher.…”
Section: Introductionmentioning
confidence: 99%